Does lesbian and gay friendliness pay off? A new look at LGBT policies and firm performance - Fatmy, Veda; Kihn, John; Sihvonen, Jukka; Vähämaa, Sami (Wiley, 2022)
We would like to thank Audur Arna Arnardottir, Kirsten Cook, Jonathan Fluharty-Jaidee, Greg Filbeck, Markku Kaustia, Christos Pantzalis, Jung Chul Park, Pontus Troberg, and conference and seminar participants at the 2019 Annual Meeting of the Southern Finance Association, the 2018 Annual Meeting of the Eastern Finance Association, the 2017 Diversity Section Meeting of the American Accounting Association, the 2017 Annual Workshop of the Nordic Corporate Governance Network, the Hanken School of Economics Workshop on Corporate Governance, the 2017 Finnish Graduate School of Finance Summer Workshop, the University of South Florida, and the University of Vaasa for valuable comments and suggestions. This work was supported by the OP Group Research Foundation, the Marcus Wallenberg Foundation, the Finnish Savings Banks Research Foundation, and the Foundation for Economic Education. Part of this paper was written while S. Vähämaa was visiting Florida Atlantic University and the University of Deusto.
Keywords: Employee policies; Firm performance; LGBT policies; sexual minorities; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|